2006
DOI: 10.1073/pnas.0602562103
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression in the mammalian eye and its relevance to eye disease

Abstract: We used expression quantitative trait locus mapping in the laboratory rat (Rattus norvegicus) to gain a broad perspective of gene regulation in the mammalian eye and to identify genetic variation relevant to human eye disease. Of >31,000 gene probes represented on an Affymetrix expression microarray, 18,976 exhibited sufficient signal for reliable analysis and at least 2-fold variation in expression among 120 F2 rats generated from an SR͞JrHsd ؋ SHRSP intercross. Genome-wide linkage analysis with 399 genetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
151
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(152 citation statements)
references
References 38 publications
1
151
0
Order By: Relevance
“…Findings from a study designed to map expression quantitative trait loci (eQTL) in the rat showed that point mutations affecting a conserved serine and another residue in the N-terminal domain of Trβ2 (Ser56Asn and His58Arg) correlated with decreases in S-opsin expression levels of as much as 30% in homozygotes (Scheetz et al, 2006). The affected residues fall within a poorly characterized ligand-independent transactivation domain that can interact with cofactors and is the target of post-translational modification in some nuclear receptors (Germain et al, 2006).…”
Section: Trβ2 Is a Positive Regulator For M-conesmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from a study designed to map expression quantitative trait loci (eQTL) in the rat showed that point mutations affecting a conserved serine and another residue in the N-terminal domain of Trβ2 (Ser56Asn and His58Arg) correlated with decreases in S-opsin expression levels of as much as 30% in homozygotes (Scheetz et al, 2006). The affected residues fall within a poorly characterized ligand-independent transactivation domain that can interact with cofactors and is the target of post-translational modification in some nuclear receptors (Germain et al, 2006).…”
Section: Trβ2 Is a Positive Regulator For M-conesmentioning
confidence: 99%
“…Trβ2 binds directly to the S-opsin promoter (Figure 3) and has been reported to interact with the basal transcription machinery as well as co-activators and co-repressors to exert complex regulatory effects on target genes (Eckey et al, 2003). The mutations identified by Scheetz et al (2006) might therefore alter one or more of these interactions, making activation of the S-opsin gene less efficient in the presence of the mutated receptor.…”
Section: Trβ2 Is a Positive Regulator For M-conesmentioning
confidence: 99%
“…In this section we illustrate the performance of MBKR-SIS through an empirical analysis of rat eye microarray expression dataset collected by Scheetz et al (2006). They experimented on 120 twelve-week-old male rats, obtained 31,042 different probe sets, and conducted genome-wide linkage analysis with 399 genetic markers.…”
Section: An Applicationmentioning
confidence: 99%
“…The dataset is available at Gene Expression Omnibus (http://www.ncbi.nlm.nih.gov/geo) with GEO accession number GSE5680. In order to gain insight into genetic variation involved in human eye disease, Scheetz et al (2006) applied expression quantitative trait locus (eQTL) mapping method to 18,976 probes that are considered Chiang et al (2006) found that the gene TRIM32 at probe 1389163 at is a critical gene to the Bardet-Biedl syndrome, which is a genetic human disease concerning about retina. Our goal is to find out which gene expression levels and genetic markers are the most predictive for the expression level of the gene TRIM32.…”
Section: An Applicationmentioning
confidence: 99%
“…These results suggest that the standardized methods are more useful than the original methods, especially when variances of predictors are substantially different. Second, we analyze the gene expression data set used by Scheetz et al (2006) to compare the prediction accuracy of the original and standardized estimators in a high-dimensional setting. This data set consists of the gene expression levels of 31,042 probe sets on 120 twelveweek-old male rats.…”
Section: Read Data Analysismentioning
confidence: 99%